2021
DOI: 10.1002/pros.24096
|View full text |Cite
|
Sign up to set email alerts
|

Risk of major adverse cardiovascular events among second‐line hormonal therapy for metastatic castration‐resistant prostate cancer: A real‐world evidence study

Abstract: BackgroundTo evaluate the possible major adverse cardiovascular events (MACE) associated with second‐line hormonal therapy in patients with metastatic castration‐resistant prostate cancer (mCRPC).MethodsWe performed a population‐based real‐world cohort study of 4962 prostate cancer patients between 2014 and 2017 utilizing the Chang Gung Research Database of Taiwan. The second‐line hormonal therapies included enzalutamide and abiraterone acetate. The outcomes of interest were MACE, including acute coronary synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Although both AA and ENZ have been shown to increase major cardiovascular events requiring hospitalization [ 18 , 57 ], namely, AA was shown to confer significantly more cardiovascular toxicities. One meta-analysis of clinical trials reported that AA confers a 2.2-fold risk of cardiovascular toxicity (RR 2.2; 95% CI 1.60–3.27) through post-treatment hospitalizations across all CVD categories examined, although mortality differences were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Although both AA and ENZ have been shown to increase major cardiovascular events requiring hospitalization [ 18 , 57 ], namely, AA was shown to confer significantly more cardiovascular toxicities. One meta-analysis of clinical trials reported that AA confers a 2.2-fold risk of cardiovascular toxicity (RR 2.2; 95% CI 1.60–3.27) through post-treatment hospitalizations across all CVD categories examined, although mortality differences were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Genitourinary disorders were also a major cause of ED visits among patients with PCa. Emerging data on the presentation of cancer populations to the ED suggest that different cancer types require different forms of medical assistance at ED visits [ 19 , 20 , 21 , 22 ]. In this study, a higher rate of ER visits in August, October, and January was observed.…”
Section: Discussionmentioning
confidence: 99%
“…We selected covariates based on the published literature 8,11,12,19,27 and expert opinions. The covariates included patients' demographics (age at index date, sex, Eastern Cooperative Oncology Group (ECOG) performance status, Gleason Score (GS), metastases), testosterone (≤0.2, 0.2-0.5, ≥0.5 ng/mL), median baseline PSA (<30, ≥30 ng/mL), other laboratory data, concomitant prescription drugs, comorbidities and healthcare utilization (Table 1).…”
Section: Covariatesmentioning
confidence: 99%
“…However, the studies produced limited results for the outcome of PSA progression free survival 8,10 and inconsistent results for overall survival (OS) in chemotherapy-naïve mCRPC patients. 8,9,[11][12][13][14] As for safety outcomes in previous clinical trials 6,7 and observational studies, [15][16][17][18][19] both ENZ and AA are associated with an increased risk of CV toxicity in patients affected by mCRPC. The extended exposure for the duration of treatments in mCRPC patients has increased concerns of CV toxicity, especially for patients who are older or with baseline CV comorbidities.…”
Section: Introductionmentioning
confidence: 99%